Time-Dependent Seismic Fragilities of Older and Newly Designed Multi-Frame Reinforced Concrete Box-Girder Bridges in California. Issue 1 (February 2019) - Abbasi, Mohammad; Moustafa, Mohamed A.
Multi-frame box-girder reinforced concrete bridge is a common bridge class in California, characterized by the use of in-span hinges, which can have adverse effects, such as the pounding of adjacent frames and deck unseating during earthquakes. The goal of this study is to develop and compare a time-dependent overall system and individual components' fragility curves of older and newly designed multi-frame reinforced concrete bridges in California. These are designed based on the pre-1971 and post-1994 seismic design specifications, respectively. Confidence bounds were developed to investigate the variability in the developed fragility curves. The study shows that older bridges have higher fragilities than new bridges at the system level, and the overall bridge system fragilities are less affected by time-dependent corrosion compared to the column fragilities. Moreover, the developed fragilities were compared to what is available in HAZUS for a better assessment of the currently available tools for this bridge type.